High-fat diet associated with obesity induces impairment of mouse corpus cavernosum responses - Toque, Haroldo A.; da Silva, Fabio H.; Calixto, Marina C.; Lintomen, Leticia; Schenka, Andre A.; Saad, Mario J.; Zanesco, Angelina [UNESP]; Antunes, Edson (Wiley-Blackwell, 2011)
What's known on the subject? and What does the study add?Erectile dysfunction (ED) is defined as the persistent inability to achieve and/or maintain an erection sufficient for satisfactory sexual performance. ED has been found in patients with cardiovascular and endocrine-metabolic diseases. Overweight, obesity and weight gain have been shown to be independent risk factors for the development of ED. Clinical studies show that ED should be considered an early clinical manifestation of risk factors for cardiovascular events, including acute myocardial infarction. However, the mechanisms that explains ED associated with obesity are yet to be fully elucidated.Using a mice model of high-fat diet associated with obesity, we have demonstrated that ED is the result of impaired endothelial and nitrergic cavernosal relaxations along with increased contractile responses, favouring penile detumescence.OBJECTIVEObesity induced by high-fat diet (HFD) is one of the most important risk factor for the development of erectile dysfunction (ED) in man. This study aimed to characterize the ED resulting from obesity associated with HFD in mice.MATERIALS and METHODSC57BL/6 mice fed for 10 weeks with either HFD to induce obesity or a standard-chow diet (SD) were used. Corpus cavernosum was surgically dissected free, and strips were mounted in 10-mL organ baths containing Krebs solution.Functional responses to endothelium-dependent and -independent agents, as well as to electrical-field stimulation were measured in the cavernosal tissue. Levels of cGMP in erectile tissue were detected by enzyme immunoassay assay.RESULTSThe potency (pEC(50)) and maximal response (E(max)) to acetylcholine were significantly lower in the HFD group compared with the SD group. A marked decrease in the non-adrenergic non-cholinergic (nitrergic) cavernosal relaxations in the HFD group was also detected. There were no significant differences between the SD and HFD groups for the cavernosal relaxations in response to sodium nitroprusside.The contractile responses elicited by the alpha(1)-adrenoceptor agonist phenylephrine were significantly greater in the HFD group compared with the SD group.Similarly, the electrical-field stimulation (2-8 Hz)-induced adrenergic contractions were markedly greater in HFD mice. The pEC(50) for endothelin-1 was about 6.9-fold higher in the HFD compared with SD group.The basal cGMP content was 47% lower in HFD strips compared with SD group. There were no morphological alterations in erectile tissue of HFD group compared with SD mice.CONCLUSIONObesity associated with HFD favours ED as result of impaired endothelial and nitrergic cavernosal relaxations along with increased contractile responses to adrenergic stimulation and endothelin-1 receptor activation.
Keywords: obesity; male impotence; nitric oxide; endothelin-1; noradrenaline; cyclic GMP